HUBUNGAN ANTARA DERAJAT KEPARAHAN STROKE DENGAN KEJADIAN STROKE-ASSOCIATED PNEUMONIA - Wandira, Rega Dwi; Amalia, Lisda; Fuadi, Iwan (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
ASSOCIATION BETWEEN STROKE SEVERITY AND STROKE-ASSOCIATED PNEUMONIAABSTRACTIntroduction: Stroke-associated pneumonia (SAP) occurs in 5-26% and decreases the quality of life and clinical outcomes of stroke patients. One of the factors that affect the incidence of SAP is the stroke severity.Aims: To determine the association between the stroke severity and the incidence of stroke-associated pneumonia in the neurological ward of Dr. Hasan Sadikin Hospital, Bandung.Methods: This is an analytic retrospective (historical) cohort design study. The study population was stroke patients who were treated in the neurological ward of Dr. Hasan Sadikin Hospital, Bandung between 2014-2016. Exclusion criteria were patient with pneumonia other than SAP and using mechanical ventilation. Stroke severity was assessed using NIHSS (National Institute of Health Stroke Scale). Chi-square was used to determine inter-variable association.Results: Among 81 subjects, 24 were assessed as SAP (29.6%). The SAP prevalence were mostly male (58.3%), age group between 65-74 year old (41.7%) with hypertension risk (87.5%), stroke onset <48 hours, lesion location on left hemisphere, onset of SAP≥48 hours, and those with consciousness impairment. Those with high stroke severity tend to have higher risk of pneumonia 3.063 times compare to patients with low stroke severity.Discussion: There was a significant association between the severity of stroke and the incidence of SAP in the neu- rological ward of Dr. Hasan Sadikin Hospital, Bandung.Keywords: NIHSS, stroke-associated pneumonia, stroke severityABSTRAKPendahuluan: Stroke-associated pneumonia (SAP) cukup sering terjadi (5-26%) pada pasien stroke, sehingga menurunkan angka kualitas hidup dan luaran klinis. Salah satu faktor yang memengaruhi kejadian SAP adalah derajat keparahan stroke.Tujuan: Mengetahui hubungan antara derajat keparahan stroke dengan kejadian SAP di Ruang Rawat NeurologiRSUP Dr. Hasan Sadikin, Bandung.Metode: Penelitian analitik dengan desain kohort retrospektif (historikal) terhadap pasien stroke iskemik yang di rawat di Ruang Rawat Neurologi RSUP Dr. Hasan Sadikin, Bandung pada tahun 2014-2016. Kriteria eksklusi adalah pasien dengan pneumonia selain SAP dan menggunakan alat ventilasi mekanik. Derajat keparahan stroke dinilai menggu- nakan skor NIHSS (National Institutes of Health Stroke Scale). Uji korelasi Chi-square digunakan untuk melihat hubungan antar-variabel.Hasil: Didapatkan 81 subjek yang 24 orang di antaranya mengalami SAP (29,6%). Prevalensi SAP tertinggi pada laki-laki (58,3%) kelompok usia 65-74 tahun (41,7%) dengan faktor risiko hipertensi (87,5%), onset stroke<48 jam, lokasi lesi di hemisfer kiri, onset SAP≥48 jam, serta pada subjek dengan penurunan kesadaran. Subjek dengan derajat keparahan stroke berat memiliki risiko terjadinya pneumonia 3,063 lebih tinggi dibandingkan dengan derajat keparahan ringan.Diskusi: Terdapat hubungan yang bermakna antara derajat keparahan stroke dengan kejadian SAP di Ruang Rawat Neurologi RSUP Dr. Hasan Sadikin, Bandung.Kata kunci: Derajat keparahan stroke, NIHSS, stroke-associated pneumonia